A Heuristic Approach to the Consecutive Ones Submatrix Problem - Rewayda Abo-Alsabeh; Hajem Ati Daham; Abdellah Salhi (مجلة بغداد للعلوم, 2023)
Given a matrix, the Consecutive Ones Submatrix (C1S) problem which aims to find the permutation of columns that maximizes the number of columns having together only one block of consecutive ones in each row is considered here. A heuristic approach will be suggested to solve the problem. Also, the Consecutive Blocks Minimization (CBM) problem which is related to the consecutive ones submatrix will be considered. The new procedure is proposed to improve the column insertion approach. Then real world and random matrices from the set covering problem will be evaluated and computational results will be highlighted.